Investor use of revised analyst information following management disclosures - Kyunbeom Jeong (Cogent Business & Management, 2020)
This study investigates the use of revised analyst forecast information that is released following management disclosures. I extend the prior literature by examining the relationship between the contents of analyst forecast revisions and the content of management disclosures. I provide evidence that investor reaction is greater in response to analyst revisions that are consistent with prior management disclosures. I also find that the amount of new information is greater in the analyst revisions that are inconsistent with management disclosures, which suggests that the inconsistency of analyst information is a result of the new information. Additionally, I find that the new information causes a more significant effect if the analyst revisions are historically more accurate than the management forecasts. These results suggest that investors consider not only the timing sequence of analyst information with respect to the corporate disclosures, but also the relationship between the analyst information and the corporate disclosure in their use of revised analyst information.
Keywords: 650; analyst forecast revision; management disclosure; investor reaction; timing sequence of information